Multi-agent system for simulation of team behaviour in product development : doctoral thesis - Perišić, Marija Majda; Podobnik, Vedran; Štorga, Mario (Zagreb : M.M. Perišić ; Fakultet elektrotehnike i računarstva, 2020)
Teams play a crucial role in many product development activities. However, teams – as complex socio-technical systems – are challenging to study in a real-world setting. Computational models and simulations offer easily controllable and cost-effective tools for supporting team studies, and prove especially valuable in studies on the sufficient conditions for the emergence of various team properties and behaviours. As a consequence, computational models offer a possible explanation of the observed phenomena and provide means for theory-testing and hypothesis generation. Thus, this work develops a computational model of team behaviour in product development with the aim of enabling computational studies of team learning and adaptation.
The dissertation develops a multi-agent system capable of representing various aspects of product development teams. Building on the existing theories, empirical studies and current teamwork models, the thesis derives a detail theoretical model of a designer, its cognition, its tasks, and interactions with others. The thesis implements the theoretical model in a multi-agent system directed at studies of the emergence of team properties and behaviours – in particular, team learning and adaptation. Extensive testing of the derived computational model concludes the goal of obtaining a multi-purpose research tool for studies of product development teams and confirms the appropriateness of the chosen simulation technique – agent-based modelling – for the intended research goal.
Keywords: Agent-based modelling and simulations; product development teams; emergent team properties; team learning; team adaptation
Timovi imaju važnu ulogu u mnogim aktivnostima razvoja proizvoda, no istraživanja timova u stvarnom okruženju dugotrajna su te izuzetno zahtjevna. Računalni modeli i simulacije omogućavaju izvršavanje velikog broja ispitivanja u kratkom vremenu, a posebno su pogodni za istraživanja kompleksnih sustava poput timova. Računalni modeli omogućavaju ispitivanje dovoljnosti uvjeta za pojavu raznih timskih svojstava i ponašanja koja proizlaze iz interakcija članova tima, nudeći objašnjenje uočenih pojava te pružajući sredstvo za testiranje postojećih teorija i stvaranje hipoteza. U ovom radu razvijen je računalni model ponašanja tima u razvoju proizvoda s ciljem omogućavanja simulacijskih studija timskog učenja i prilagodbe.
U radu je razvijen višeagentski sustav za simulaciju ponašanja tima u razvoju proizvoda. Oslanjajući se na teorije, empirijske studije i postojeće modele timskog rada, u disertaciji je opisan teorijski model člana razvojnog tima s posebnim naglaskom na prikaz njegovih kognitivnih procesa, teorijski model konstrukcijskih problema te model interakcija među članovima tima u razvoju proizvoda. Na temelju teorijskog modela izrađen je računalni prototip čija je svrha proučavanje raznih timskih svojstava, a posebice timskog učenja i adaptacije. Opsežnim testiranjem razvijenog računalnog modela omogućeno je postizanje cilja ovog rada: stvaranje višenamjenskog istraživačkog alata za proučavanje timova u razvoju proizvoda te je potvrđena prikladnost odabrane tehnike simulacije – modeliranja zasnovanog na agentima – za ostvarenje navedenog cilja.
Ključne riječi: Modeliranje i simulacije zasnovane na agentima; timovi u razvoju proizvoda; svojstva tima koja proizlaze iz interakcija njegovih članova; timsko učenje; timska prilagodba.
Bibliografija str. 174-207.